Creativity: Re-thinking Professional Discretion - Tony Evans (Social Work and Society, 2020)
Discretion is often characterized as a negative phenomenon, arbitrary action in the absence of rules. This view obscures another approach to discretion, as a site of creativity where professionals work with citizens to meet their needs and make welfare services anew. These different conceptions of discretion relate to different ecologies of welfare production. Discretion as creativity has played an essential role in the welfare state, but has been pushed aside by more limited conceptions as welfare services have become more managerialized. It’s vital to revisit the connections between creativity and discretion and consider how it can help us better understand the potential for practitioners to craft responsive and empowering services in their work with citizens. Creative discretion entails problem-solving, imagination, and understanding and engaging with other people’s perspectives. Recognizing this approach to discretion supports the innovative dimension of practice. It also underlines the role practitioners play in making policy on the ground in a way that engages with the diverse social world within which they operate.